Pengaruh Manajemen Modal Kerja, Pertumbuhan Penjualan dan Ukuran Perusahaan Terhadap Profitabilitas Pada Perusahaan Properti dan Real Estate Yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2010-2014 - Suryaputra, Gladys (Business Accounting Review, 2016)
This study aimed to examine the influence of working capital management, sales growth, and firm size on profitability in property and real estate companies listed in the Indonesian Stock Exchange in the period of 2010-2014. This study was conducted on 36 property and real estate companies that published annual report in the period of 2010-2014 that used Rupiah. This study was a quantitative research by using multiple linear regression analysis with SPSS software version 16.0.The study concluded that sales growth (SG) had significant influence on ROA. While the working capital management that was proxied into the cash conversion cycle (CCC), and firm size (SIZE) were proved did not have significant influence on ROA in the property and real estate companies listed in the Indonesian Stock Exchange in the period of 2010-2014. The implication of this study supporting the analysis theory of DuPont.